2018
DOI: 10.1002/cyto.a.23353
|View full text |Cite
|
Sign up to set email alerts
|

A flow cytometry‐based assay to determine the phagocytic activity of both clinical and nonclinical antibody samples against Chlamydia trachomatis

Abstract: Globally, an estimated 131 million new cases of chlamydial infection occur annually. Chlamydia trachomatis infection can cause permanent damage to the fallopian tubes in woman, resulting in infertility and a risk of ectopic pregnancy. There is a great need for a vaccine against Chlamydia trachomatis and as a result there is a need for assays to evaluate functional immune responses for use in future clinical trials and epidemiological studies. Antibodies play a crucial role in the defense against infection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…is more than direct blocking of infection, i.e., by neutralization. A range of other indirect effector functions like opsonophagocytosis 54 , antibody-dependent complement deposition (ADCD) 55 , 56 , antibody-dependent cellular cytotoxicity (ADCC) 42 , or combinations thereof could potentially play a role. In this study, we demonstrated an in vivo protective effect of antibodies by preincubating C.t .…”
Section: Discussionmentioning
confidence: 99%
“…is more than direct blocking of infection, i.e., by neutralization. A range of other indirect effector functions like opsonophagocytosis 54 , antibody-dependent complement deposition (ADCD) 55 , 56 , antibody-dependent cellular cytotoxicity (ADCC) 42 , or combinations thereof could potentially play a role. In this study, we demonstrated an in vivo protective effect of antibodies by preincubating C.t .…”
Section: Discussionmentioning
confidence: 99%
“…The blood samples used for analyses were collected before the start of all vaccinations (day 0) and after the end of the last vaccination (day 29). Total antibody production specific for the NDV vaccine was determined in serum using commercial enzyme-linked immunosorbent assay (ELISA) kits (46). The antibody response was measured by the hemagglutination inhibition (HI) test (47).…”
Section: Criteria Of Responsementioning
confidence: 99%
“…The phagocytic index indicates the strength of the phagocytic cell, represented by the number of the ingested bacteria. Phagocytic activity is considered as the first line of defense against antigens and pathogenic agents (33,34). Total antibody production specific for NDV vaccine was determined in serum using commercial ELISA kits (35).…”
Section: Immune Indicesmentioning
confidence: 99%